A NEW READING OF IMAM SADIQ'S DEBATES BASED ON INTERTEXTUALITY OF GENETTEE THEORY - Iranmanesh, Asma; Zarezardini, Ahmad; Sahraei Ardakani, Kamal (State Islamic University of Datokarama Palu, 2023)
The aim of this study is to discuss the new reading of Imam Saddiq debate based on intertextuality of Genette Theory. Imam Sadiq (peace be upon him) engaged in discussions with various people during his lifetime and tried to show the truth based on the book and religion of his grandfather, the Messenger of God. This study used content analysis approach to analyse Imam Sadiq though and the results of the study was presented based on themes found in the data. The findings of this study shows that theories of Intertextuality, including the Intertextual theory of Kristova and Barthes and the theory of Genette's trans textuality, are new approaches to reading and criticizing texts. Genette proposed his theory of trans textuality on five bases, and intertextuality is one of his bases. After briefly introducing the theories of trans textuality using Genet's theory of intertextuality, this article deals with a new reading of Imam Sadiq's debates with different people. Using the descriptive-analytical method, it examines the text of the discussions with the verses and concepts of the Holy Quran, and the types of relationships intertextuality, expresses them.